The Interplay Between Kidney Dysfunction and Pulmonary Edema: The Role of Body Position - Dung, Abhilash Dung; Neha Negi; Sasanka Sekhar Pradhan (Gayaku Publisher, 2024)
Pulmonary edema represents a significant complication in patients with kidney dysfunction, affecting approximately 35% of individuals with advanced renal disease (Hsu et al., 2006). This comprehensive review examines the pathophysiological mechanisms connecting pulmonary edema with kidney dysfunction and evaluates how body positioning influences respiratory symptoms. Recent clinical data suggests that appropriate positioning strategies can reduce respiratory distress by up to 40% in affected patients (Huang et al., 2012), highlighting the importance of this non-invasive intervention in clinical management. Understanding these relationships is crucial for improving patient outcomes and optimizing clinical practice protocols.